2020
DOI: 10.3389/fcell.2020.588023
|View full text |Cite
|
Sign up to set email alerts
|

TPP1 Enhances the Therapeutic Effects of Transplanted Aged Mesenchymal Stem Cells in Infarcted Hearts via the MRE11/AKT Pathway

Abstract: Background: Poor cell survival after transplantation restricts the therapeutic potential of mesenchymal stem cell (MSC) transplantation into infarcted hearts, particularly in older individuals. TPP1, a component of the shelterin complex that is involved in telomere protection, is highly expressed in young MSCs but declines in aged ones. Here, we explore whether TPP1 overexpression in aged mouse MSCs improves cell viability in vivo and in vitro. Methods: Aged mouse MSCs overexpressing TPP1 were injected into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Previous studies have reported that ADSCs can improve photoaging wrinkles and promote collagen production in photoaged fibroblasts in vitro [ 5 , 6 ]. Despite the tremendous achievements of stem cell therapy, there are still some challenges in clinical application, especially the low survival rate after transplantation [ 10 , 11 ]. So, there is an urgent need to find better ways to use stem cells in the clinic.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that ADSCs can improve photoaging wrinkles and promote collagen production in photoaged fibroblasts in vitro [ 5 , 6 ]. Despite the tremendous achievements of stem cell therapy, there are still some challenges in clinical application, especially the low survival rate after transplantation [ 10 , 11 ]. So, there is an urgent need to find better ways to use stem cells in the clinic.…”
Section: Introductionmentioning
confidence: 99%
“…It uncovered more than 1000 clinical trials when we searched the keywords "mesenchymal stem cell" or "mesenchymal stromal cell" in the ClinicalTrials.gov database (http://www.clinicaltrials.gov/, accessed on June 2021). Despite the tremendous achievements made in MSCs therapy [3,[7][8][9][10][11], there are several limitations toward their clinical translation, such as invasive cell collection procedures, orchestrated engraftment steps, low posttransplantation cell viability, poor homing, and multiple doses to maintain the therapeutic effects [12][13][14][15]. Promisingly, accumulating experimental and clinical studies reveal that the powerful therapeutic agents of MSCs are mainly exerted by their paracrine effects, in particularly by exosomes [13,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…MRE11 has been recently identified as a TPP1 downstream target [ 15 ]. In addition to enhancing DNA repair and improving cell survival [ 15 ], MRE11 is also required for cell proliferation [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…MRE11 has been recently identified as a TPP1 downstream target [ 15 ]. In addition to enhancing DNA repair and improving cell survival [ 15 ], MRE11 is also required for cell proliferation [ 16 ]. In human breast cancer cells, MRE11 regulates cell proliferation via signal transducer and activator of transcription 3 (STAT3) [ 17 ].…”
Section: Discussionmentioning
confidence: 99%